Analisis Kesadaran Cyber Security di Kalangan Pengguna Layanan Keuangan Digital Indonesia - Maulida Farahanita; Chanief Budi Setiawan; Rama Sahtyawan; Nurul Fatimah (Jurnal Teknomatika, 2022)
The rapid development of information technology has led most people to choose to use digital banking and financial services to carry out various financial transactions. The most common crimes that occur are in the banking industry, including hacking (hacking of digital services), skimming (copying data information from digital service users), defacing (replacing or modifying digital service pages), phishing (deception of digital service users), BEC (business email compromise), and social engineering (social engineering to digital service users). To measure the level of cyber security awareness among users of digital financial services in Indonesia using the AHP method. This research is a quantitative study by distributing online questionnaires, then analyzed using the AHP method to find out which criteria have the highest or lowest scores. The largest weight of these criteria is knowledge of 0.5009, then sequentially is attitude of 0.3307, and behavior of 0.173. Digital financial service users already have insight or knowledge regarding how to maintain the security of their personal data, but it is still lacking in its application, so it is necessary to conduct in-depth re-education regarding the big risks given by carelessly maintaining privacy data. On the Attitude criteria; users still save PIN/passwords in smartphone notes, install applications outside the Play Store or App Store, rarely update the operating system on their smartphones, and leave their smartphones to other people or public places. On the Behavior criteria; users still use the same PIN/password on different accounts.